Development of Audiobook Learning Media on Solfeggio for Music Skills of Visually Impaired Students - Muhammad Rofi’u Zaky; Endang Purbaningrum; Murtadlo (IJE : Interdisciplinary Journal of Education, 2023)
This study aims to (1) produce an audiobook learning media on solfeggio for the music skills of visually impaired students, (2) analyze the feasibility of the audiobook learning media product on solfeggio for the music skills of visually impaired students, (3) analyze the practicality of the audiobook learning media product on solfeggio for the music skills of visually impaired students, and (4) analyze the effectiveness of the audiobook learning media product on solfeggio for the music skills of visually impaired students. This research employs Research and Development (R&D) methodology with the ADDIE procedure. Data collection techniques in this study involve the use of questionnaires, and data analysis techniques include validity, practicality, and effectiveness testing. The Validation Test of the audiobook learning media on solfeggio has been proven to be acceptable according to content experts, with a score of 82%. It is also considered highly suitable by media experts, with a score of 89%. Moreover, it is regarded as practical by practitioners, obtaining a score of 93%. The effectiveness test resulted in a mean range of 0.6, demonstrating its effectiveness in improving the learning outcomes of visually impaired students.